Rola inkulturacji w nowej ewangelizacji - Nowicka, Justyna (Annales Missiologici Posnanienses, 2023)
The article includes an attempt to describe the relationship between inculturation and the new evangelization, focusing on inculturation as a method of the new evangelization. In the literature of the subject there are many studies on inculturation in indigenous cultures of Africa or Latin America. However, there is little scientific literature on contemporary culture, which is also the subject of missionary activities of the Church. Therefore there is a need to systematize and investigate this topic. As a result of the analysis, the article shows that it is possible to use analogies in the application of inculturation, and it is possible to speak of inculturation in the new evangelization. An outline of the areas of contemporary culture is also presented which particularly require evangelization and inculturation.